The Effect of Management Earnings Forecasts on the Relationship between Returns and Future Earnings and the Implications for the Continuation of Management’s Quarterly Earnings Guidance - Choi, Jong-Hag (Institutional Knowledge at Singapore Management University, 2008)
Using a sample of 11,897 firm-year observations from 1998 through 2001, we build on literature suggesting that more informative disclosures allow returns to better reflect future earnings, and test whether the issuance of management forecasts and the characteristics of those forecasts influence the future earnings response coefficient (FERC). We find that FERCs are greater for firms that forecast earnings and for firms that forecast more frequently and/or more precisely, suggesting that more frequent and more precise forecasts assist investors in better predicting future earnings. Importantly, we also find that quarterly forecasts and short-term forecasts incrementally increase the association between returns and future earnings beyond annual and long-term forecasts, indicating that even short-term, quarterly forecasts allow investors to form better expectations about future earnings. This latter finding suggests a benefit of quarterly earnings forecasts that may have been overlooked in recent recommendations from the United States (U.S.) Chamber of Commerce, the CFA Institute, the Business Roundtable Institute for Corporate Ethics, and The Conference Board to eliminate quarterly earnings guidance.